2016
DOI: 10.15376/biores.11.3.7737-7753
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Merbau Extractives as a Potential Wood-Impregnating Material

Abstract: aThis study aimed to investigate the major content of merbau extractives (ME) and their potential use as an impregnating material for low-quality timber. Extraction was done by maceration with ethanol, ethyl-acetate, and hot-water. Physico-chemical, phyto-chemical, UV-visible, and infrared spectroscopy, as well as py-GCMS analysis were then performed on dried extract. The results showed that organic solvent extractions resulted in much higher yields, by 12.50% than that of hot water (1.10%). The merbau extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…For example, Malik and Santoso reported extraction efficiencies in the range of 0.7% to 6.7% for oily keruing wood samples using solutions of water and ethanol in various proportions. Malik et al reported that the extraction yield of merbau extractives were 12.45%, 12.56%, and 1.34% when 80% ethanol, 60% ethyl acetate, and hot water were used, respectively. The organic solvents increase the extractive efficiency due to the fact that their polar and nonpolar functional groups dissolve more complicated compounds, such as tannins, resins, wax, and gum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Malik and Santoso reported extraction efficiencies in the range of 0.7% to 6.7% for oily keruing wood samples using solutions of water and ethanol in various proportions. Malik et al reported that the extraction yield of merbau extractives were 12.45%, 12.56%, and 1.34% when 80% ethanol, 60% ethyl acetate, and hot water were used, respectively. The organic solvents increase the extractive efficiency due to the fact that their polar and nonpolar functional groups dissolve more complicated compounds, such as tannins, resins, wax, and gum.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent choice should depend on the targeted extracted compounds and/or the purpose of the extraction. From a general environmental point of view, water is better than organic solvents, because it is relatively cheap, nontoxic, inflammable, and recyclable . As the primary purpose of this work was characterizing the water‐soluble materials in wood veneers, water was the best choice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first (1) and the second (2) extracts were combined to make a concentrate (with the use of a rotary evaporator), which was freeze-dried to powder. The properties the ME have been thoroughly investigated by Malik et al (2016). Hot water was used as the solvent in this study because according to Kislik (2012), water is the best alternative for organic solvent.…”
Section: Impregnating Materials and Treatmentmentioning
confidence: 99%
“…This procedure was applied for the samples of the three impregnating solutions (ME, PME22 and PME33). After that, all specimens were drained and then put into a conditioning room until a constant weight was reached (Malik et al 2015, Malik et al 2016, Malik et al 2018. The moisture content of all tested samples was 12% to avoid -according to Rowell (1996) -a misleading or even invalid values if the samples were tested at different moisture levels.…”
Section: Impregnating Materials and Treatmentmentioning
confidence: 99%